2015
DOI: 10.1007/s10549-015-3649-z
|View full text |Cite
|
Sign up to set email alerts
|

184AA3: a xenograft model of ER+ breast adenocarcinoma

Abstract: Purpose Despite the prevalence and significant morbidity resulting from estrogen receptor positive (ER+) breast adenocarcinomas, there are only a few models of this cancer subtype available for drug development, and arguably none for studying etiology. Those models that do exist have questionable clinical relevance. Methods Given our goal of developing luminal models, we focused on six cell lines derived by minimal mutagenesis from normal human breast cells, and asked if any could generate clinically relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The tumorigenic cell line 184AA3 emerged from 184Aa following insertional mutagenesis that inactivated p53 function (Stampfer et al, 2003 ). It exhibits increased genomic instability and forms clinically relevant ER+ luminal adenocarcinomas in the mouse xenograft model (Stampfer et al, 2003 ; Hines et al, 2016 ). To evaluate how the HMEC progression series responds to normal-like and stroma-like microenvironments, we cultured single cell suspensions in laminin-rich ECM [lrECM (matrigel)] and COL1 3D gels, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The tumorigenic cell line 184AA3 emerged from 184Aa following insertional mutagenesis that inactivated p53 function (Stampfer et al, 2003 ). It exhibits increased genomic instability and forms clinically relevant ER+ luminal adenocarcinomas in the mouse xenograft model (Stampfer et al, 2003 ; Hines et al, 2016 ). To evaluate how the HMEC progression series responds to normal-like and stroma-like microenvironments, we cultured single cell suspensions in laminin-rich ECM [lrECM (matrigel)] and COL1 3D gels, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Shinoda et al have shown prognostic significance of ER, HER2 and caveolin-1 IHC in canine mammary gland tumors, which mirrors prognostic data for humans [208]. An example of improved animal modelling is the currently available xenograft model of ER+ breast adenocarcinoma that maintains an intact microenvironment [209]. This model recapitulates breast architecture which is critical for decoding spatial and temporal tumor-stromal interactions.…”
Section: Five-year Viewmentioning
confidence: 99%
“…We used two well-known cellular models of ERα-positive human breast adenocarcinoma: MCF7 and T47D. These cell lines have been widely used and validated for the study of ERα activity because primary culture of normal or tumor human breast tissues leads to the loss of ERα expression (Graham et al, 2009; Hines et al, 2016). We demonstrate that FN prolongs ERα half-life and strengthens its transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%